Decision Support System For Selection Of Productive At Sahabat Sampulo Foundation Using The Profile Matching Method - Nia Nandara; Rahman Rahman; Adhy Rizaldy (Journal of Computer Engineering, Electronics and Information Technology, 2023)
The Sahabat Sampulo Foundation is dedicated to supporting and empowering underprivileged individuals by providing them with opportunities to engage in productive activities. However, the process of selecting the most suitable individuals for various productive projects can be challenging due to the large number of applicants and the diverse range of skills required. To address this issue, a Decision Support System (DSS) utilizing the Profile Matching Method is proposed. Making decisions is one of the most basic things in everyday life, in the decision-making process humans are often faced with many alternatives to choose from, so that in a problem, several decision makers can make different decisions. The advancement of this technology has also been put to good use by the Sahabat Sampulo Foundation to determine the selection of productive and unproductive employees. Because it still uses traditional methods subjectively and manually, from these problems a system is needed that can help determine employee data decisions for the Sahabat Sampulo Foundation. This Profile Matching method compares the value and actual data of a profile that will be assessed with the profile value that is applied.